Pengaruh Brand Image, Ewom dan Brand Awareness Terhadap keputusan Pembelian Produk Kosmetik Wardah Batam - Indah Lahitani Natasya Dasopang; Sunargo Sunargo (STIE AMKOP, 2023)
This study aims to find out how brand image, ewom and brand awareness have an influence on purchasing decisions. The method used in this research is to use quantitative research methods. The population in this study are consumers who have purchased Wardah cosmetic products of the Suncreen type in Sungai Jodoh Village, Batam. The sampling technique in this study was to use a purposive sampling method with a sample of 100 respondents. The data analysis technique used is multiple linear regression analysis. The test results show that brand image and brand awareness have a significant effect on purchasing decisions, while ewom has no significant effect on purchasing decisions. Based on the results of the calculation of the coefficient of determination adjusted (R2) a value of 0.666 is obtained. This is able to explain the purchase decision variable of 66.5%. While it can be said that 66.5% of the purchasing decision variables can be explained by the temporary model and the remaining 33.4% is influenced by other factors that are not included in this study Kata Kunci : Brand image, Ewom, Brand Awarness and purchasing decisions